Comparative Biotypic and Phylogenetic Profiles of Escherichia coli Isolated from Resident Stool and Lagoon in Fresco (Côte d’Ivoire) - Nadége Kouadio-Ngbesso; Koua Atobla; Paul Yao Attien; Mireille Kouame-Sina; René Ahua Koffi; Antoinette Ama Adingra; Adjehi Dadié (International Journal of Microbiology)
Anthropogenic activities could expose Fresco lagoon to microbial pollution. The objective of this study was to determine the level of pollution in Fresco lagoon related to fecal contaminations. Two hundred and seventy (270) samples including 216 water and 54 human stools samples from local residents were collected. Escherichia coli was isolated and identified according to classical bacteriology procedure. Strains were characterized by biotyping on API 20E gallery and phylogenetic typing by PCR triplex of Clermont. A set of 392 strains of E. coli was distributed into 18 biotypic profiles. Five biotypes were common to water and human. Classification of all biotypes revealed close relationship between water and human strains because of their repartition in the same groups. Phylogenetic groups A, B1, B2, and D were identified in all strains. Strains belonging to phylogenetic group A were most frequent in water (69.82%) and human stool (44.44%) followed by group B1 in water (24%) and human stool (40.7%). Strains of group B2 were scarce in water (4.4%) and humans (7.41%). The diversity of E. coli biotypes observed in this study revealed animal and human origins of contaminations. A close relationship was found between water and human strains, and the presence of commensal and extraintestinal pathogenic E. coli in all samples could represent a potential reservoir of extraintestinal infections for resident populations.